'Anything is Possible': Rethinking the Politics of Transition through a Poetics of Failure in the Works of William Kentridge and Dmitry Gutov. Issue 5 (1st November 2016) - Robbe, Ksenia
Abstract: The metaphor of transition has produced one of the most powerful images that captured the global historical momentum of the late twentieth century. Even though its teleological implications have been critiqued, we still live in the shadow of transition, or rather its incipient failures, as the global media represent countries that embarked on processes of transformation as relapsing and returning to primordial states. This article inquiries into the ways in which artists from two global peripheries – William Kentridge (South Africa) and Dmitry Gutov (Russia) – resist these homogenising discourses by critically engaging with failures of the transitions. A comparative reading of the artists' works from the past decade suggests that they develop a poetics which, drawing on the legacies of absurdism, treats failure as productive opportunity. Approaching the problems of transformation by remembering earlier revolutionary projects and inquiring into their politics of time, these works unravel creative possibilities within what has been deemed failed.